2018
DOI: 10.1038/s41467-018-03506-3
|View full text |Cite
|
Sign up to set email alerts
|

Hunting regulation favors slow life histories in a large carnivore

Abstract: As an important extrinsic source of mortality, harvest should select for fast reproduction and accelerated life histories. However, if vulnerability to harvest depends upon female reproductive status, patterns of selectivity could diverge and favor alternative reproductive behaviors. Here, using more than 20 years of detailed data on survival and reproduction in a hunted large carnivore population, we show that protecting females with dependent young, a widespread hunting regulation, provides a survival benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 57 publications
(87 reference statements)
5
64
1
Order By: Relevance
“…We demonstrated that black bears are exposed to high levels of anthropogenic mortality in large portions of their range, and how harvest can influence other types of anthropogenic mortality. Even in partially recovered and sustainably managed carnivore populations, regulated hunting can still influence their ecology 61,91 . On the other hand, poaching is often lower within protected areas (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that black bears are exposed to high levels of anthropogenic mortality in large portions of their range, and how harvest can influence other types of anthropogenic mortality. Even in partially recovered and sustainably managed carnivore populations, regulated hunting can still influence their ecology 61,91 . On the other hand, poaching is often lower within protected areas (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In many areas, the killing of females with dependent offspring is prohibited or discouraged (e.g. 56,59,60 which can cause life history alterations 61 . Many wildlife species are managed expecting hunting mortality to trigger density-dependent responses in reproduction, survival, and population growth (compensatory mortality hypothesis 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…By prolonging the period of maternal care, females can provide protection to yearlings from both conspecifics and hunters (Van de Walle et al, 2018). Furthermore, legal hunting pressure is high in the South, which, combined with the legal protection of family groups, provides a survival advantage to females and their cubs when maternal care is extended (Van de Walle et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…African elephant; Lee & Moss, 1986). Despite having the potential to affect long-term reproductive success and fitness of individual females (Balme et al, 2017;Van de Walle et al, 2018), our knowledge of the causal mechanisms leading to variation in the duration of maternal care is surprisingly limited. Lee et al (1991) showed in a comparative analysis that offspring age and mass at weaning are correlated across species, with offspring being weaned at the threshold mass of about four times their neonatal mass.…”
mentioning
confidence: 99%
“…Close seasons can help protect dependent young. In Finland and Sweden female bears with cubs and cubs younger than one year are protected [59,60].…”
Section: Impacts On Non-target Animalsmentioning
confidence: 99%